A dynamic reconfiguration manager for graph-oriented distributed programs - Jiannong Cao; Chan, E.; Lee, C.H.; Yu, K.W. (Parallel and Distributed Systems (ICPADS '97): Proceedings of the 1997 International Conference, 1997)
Dynamic reconfiguration allows the system configuration to be changed while the system is in execution. It is definitely a desirable property for any large distributed system where dynamic modification and extension to the system and its applications are required. We have developed a software platform based on a graph-oriented model, which provides support for programming reconfigurable distributed applications. In this paper, we describe a dynamic reconfiguration manager for the graph-oriented distributed programming environment. The services and requirements of dynamic reconfiguration are identified, the architecture design of a dynamic reconfiguration manager is presented, and a central server-based prototypical implementation of the manager on a local area network of workstations is described.